THE TEACHER PROBLEMS ANALYSIS OF CRITICAL THINKING SKILLS, LEARNING MOTIVATION AND STUDENT LEARNING OUTCOMES - Ria Oktaviani; Elsje Theodora Maasawet; Krishna Purnawan Candra (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2021)
The low critical thinking skills, learning motivation and student learning outcomes are the background of this observation. Observations were made on biology teachers and class XI students at SMA Negeri 17 Samarinda, SMA Negeri 5 Samarinda, and SMA Negeri 1 Long Ikis. Based on the results of the teacher and student response questionnaires, several problems were obtained in classroom learning, including the lack of student motivation, due to conventional learning (lecture methods and less variety), the lack of opportunities for students to express ideas, and the lack of learning resources. The purpose of this study was to examine problems related to the level of critical thinking skills, learning motivation, and student learning outcomes. The research subjects were biology teachers and class XI students at SMA Negeri 17 Samarinda, SMA Negeri 5 Samarinda, and SMA Negeri 1 Long Ikis. The results showed that the critical thinking skills of SMA Negeri 17 Samarinda students were 70.68% (medium predicate), SMA Negeri 5 Samarinda was 71.49% (medium predicate) and SMA Negeri 1 Long Ikis was 71.09% (medium predicate). Furthermore, the data analysis of students' learning motivation of SMA Negeri 17 Samarinda, SMA Negeri 5 Samarinda, and SMA Negeri 1 Long Ikis respectively were as follows 78.64%, 79.92%, and 78.05% with the same predicate, namely good. Then the student learning outcomes showed SMA Negeri 17 Samarinda was 77.73% (enough predicate), SMA Negeri 5 Samarinda was 78.27% (enough predicate) and SMA Negeri 1 Long Ikis was 78.35% (enough predicate). students at SMA Negeri 17 Samarinda, SMA Negeri 5 Samarinda, and SMA Negeri 1 Long Ikis it can be concluded that the results of critical thinking skills, learning motivation, and student learning outcomes without using learning media have a major influence on the learning process.